NIR-II live imaging study on the degradation pattern of collagen in the mouse model. (13th December 2022) - Li, Huizhu; Meng, Xinxian; Sheng, Huaixuan; Feng, Sijia; Chen, Yuzhou; Sheng, Dandan; Sai, Liman; Wang, Yueming; Chen, Mo; Wo, Yan; Feng, Shaoqing; Baharvand, Hossein; et al.
Abstract: The degradation of collagen in different body parts is a critical point for designing collagen-based biomedical products. Here, three kinds of collagens labeled by second near-infrared (NIR-II) quantum dots (QDs), including collagen with low crosslinking degree (LC), middle crosslinking degree (MC) and high crosslinking degree (HC), were injected into the subcutaneous tissue, muscle and joints of the mouse model, respectively, in order to investigate the in vivo degradation pattern of collagen by NIR-II live imaging. The results of NIR-II imaging indicated that all tested collagens could be fully degraded after 35 days in the subcutaneous tissue, muscle and joints of the mouse model. However, the average degradation rate of subcutaneous tissue ( k = 0.13) and muscle ( k = 0.23) was slower than that of the joints (shoulder: k = 0.42, knee: k = 0.55). Specifically, the degradation rate of HC ( k = 0.13) was slower than LC ( k = 0.30) in muscle, while HC showed the fastest degradation rate in the shoulder and knee joints. In summary, NIR-II imaging could precisely identify the in vivo degradation rate of collagen. Moreover, the degradation rate of collagen was more closely related to the implanted body parts rather than the crosslinking degree of collagen, which was slower in the subcutaneous tissue and muscle compared to the joints in the mouse model. Graphical abstract: